18F-fluorodeoxyglucose Positron Emission Tomography in Kaposi Sarcoma Herpesvirus–Associated Multicentric Castleman Disease: Correlation With Activity, Severity, Inflammatory and Virologic Parameters. (31st March 2015) - Polizzotto, Mark N.; Millo, Corina; Uldrick, Thomas S.; Aleman, Karen; Whatley, Millie; Wyvill, Kathleen M.; O'Mahony, Deirdre; Marshall, Vickie; Whitby, Denise; Maass-Moreno, Roberto; Steinberg, Seth M.; Little, Richard F.; et al.
Abstract: Background.  Kaposi sarcoma herpesvirus (KSHV)-associated multicentric Castleman disease (MCD) is a lymphoproliferative inflammatory disorder commonly associated with human immunodeficiency virus (HIV). Its presentation may be difficult to distinguish from HIV and its complications, including lymphoma. Novel imaging strategies could address these problems. Methods.  We prospectively characterized 18 F-fluorodeoxyglucose positron emission tomography (PET) findings in 27 patients with KSHV-MCD. Patients were imaged with disease activity and at remission with scans evaluated blind to clinical status. Symptoms, C-reactive protein level, and HIV and KSHV loads were assessed in relation to imaging findings. Results.  KSHV-MCD activity was associated with hypermetabolic symmetric lymphadenopathy (median maximal standardized uptake value [SUVmax ], 6.0; range, 2.0–8.0) and splenomegaly (3.4; 1.2–11.0), with increased metabolism also noted in the marrow (2.1; range, 1.0–3.5) and salivary glands (3.0; range, 2.0–6.0). The 18 F-fluorodeoxyglucose PET abnormalities improved at remission, with significant SUVmax decreases in the lymph nodes ( P = .004), spleen ( P = .008), marrow ( P = .004), and salivary glands ( P = .004). Nodal SUVmax correlated with symptom severity ( P = .005), C-reactive protein level ( R = 0.62; P = .004), and KSHV load ( R = 0.54; P = .02) but not HIV load ( P = .52). Conclusions.  KSHV-MCD activity is associated with 18 F-FDG PET abnormalities of the lymph nodes, spleen, marrow, and salivary glands. These findings have clinical implications for the diagnosis and monitoring of KSHV-MCD and shed light on its pathobiologic mechanism.